Paternal aggression in a biparental mouse: Parallels with maternal aggression - Trainor, Brian C. (2007)
Environmental and social factors have important effects on aggressive behaviors. We examined the effect of reproductive experience on aggression in a biparental species of mouse, Peromyscus californicus. Estrogens are important in mediating aggressive behavior so we also examined estrogen receptor expression and c-fos for insights into possible mechanisms of regulation. Parental males were significantly more aggressive than virgin males, but no significant differences in estrogen receptor alpha or beta expression were detected. Patterns of c-fos following aggression tests suggested possible parallels with maternal aggression. Parental males had more c-fos positive cells in the medial amygdala, and medial preoptic area relative to virgin males. The medial preoptic area is generally considered to be relatively less important for male-male aggression in rodents, but is known to have increased activity in the context of maternal aggression. We also demonstrated through habituation–dishabituation tests that parental males show exaggerated investigation responses to chemical cues from a male intruder, suggesting that heightened sensory responses may contribute to increased parental aggression. These data suggest that, in biparental species, reproductive experience leads to the onset of paternal aggression that may be analogous to maternal aggression.